Glaucoma Associated with Boston Type 1 Keratoprosthesis - Kamyar, Roheena (2012)
PURPOSE: To evaluate outcomes of the Boston Type 1 keratoprosthesis (KPro) and associated incidence of glaucoma. DESIGN: Retrospective cohort study. PARTICIPANTS: All patients who underwent KPro surgery at one institution from 2003-2009 with at least 3 months follow-up. METHODS: Preoperative visual acuity, diagnosis, history of glaucoma, intraoperative and postoperative parameters were recorded. Statistical analysis was performed to identify factors that may influence increase in intraocular pressure (IOP) and glaucoma development or progression after surgery. MAIN OUTCOME MEASURES: Best corrected visual acuity (BCVA), IOP, postoperative medical and surgical treatments for glaucoma, and KPro retention and complications. RESULTS: Thirty-six KPro procedures were performed in 30 eyes of 29 patients with mean (± SD) follow-up of 17±19 months (range 3-67 months). The main indication for KPro implantation was corneal graft failure (77%). Primary KPros were performed in 23% of eyes for limbal stem cell deficiency secondary to chemical burns and aniridia, and for herpetic disease. Median preoperative BCVA was hand motions with an overall improvement to 20/330 (range 20/20 to hand motions) at nine months postoperatively; mean BCVA was 20/600 (range 20/40 to NLP) at last follow-up. Twenty eyes (67%) had a preoperative history of glaucoma with eight of those eyes (40%) having undergone prior glaucoma surgery. Twenty-one eyes (70%) underwent concomitant glaucoma surgery. Postoperative increased IOP (22 mmHg or higher) was noted in 15 eyes (50%) while definite glaucoma development or progression was noted in 7 of those 15 eyes (23% of total eyes). Mean BCVA at last follow-up in eyes with glaucoma development or progression was 3/200 compared to 20/563 in the remaining 23 eyes. Six patients (20%) required repeat KPro implantation, and retroprosthetic membranes developed in 23 eyes (77%). No patient developed vitritis or infectious endophthalmitis. CONCLUSIONS: The Boston Type 1 KPro is an effective option for management of eyes with poor prognosis for primary or repeat penetrating keratoplasty. Visual potential is limited by preoperative comorbidities; however, glaucoma development or progression of pre-existing glaucoma is a significant cause of postoperative visual loss. Rigorous perioperative management of elevated IOP is essential for long-term success of KPro surgery.